ARANG AKTIF SERAT SABUT KELAPA DAN APLIKASINYA SEBAGAI ADSORBEN ION KROMIUM(III) DARI LARUTAN AIR - Manuntun Manurung; Widihati Widihati; I.A.G. Yunilawati (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2022)
The coconut husk contains high cellulose, so it can be processed as a basic materials to make activated charcoal. The purpose of the study was to make activated charcoal from coconut husk fiber with hydrochloric acid activator and to determine the effect of changing coconut husk fiber into charcoal, as well as activation of the adsorption power of Cr(III) metal ions from solution. The research started by separating the coconut husk fiber, carbonization at various temperatures. The resulting charcoal was characterized according to SNI 06-3730-1995. The best quality charcoal was activated with HCl, then coconut husk fiber, unactivated and activated charcoals were applied to absorb Cr(III) ions. Optimization of adsorption parameters such as contact time, solution pH, temperature and adsorption isotherm were also studied. The results showed that the optimum carbonization temperature was 600oC, contact time was 5 hours, optimum pH was 6, room temperature. The adsorption capacity of Cr(III) ions were 8.2580 mg/g, 13.5645 mg/g and 16.1452 mg/g for coconut husk fiber, unactivated and activated charcoal, respectively. The increase in adsorption power from coconut husk fiber to charcoal was 64.36% and from charcoal to activated charcoal increased by 19.02%. Coconut husk fiber and unactivated charcoal followed the Langmuir isotherm while activated charcoal followed Freundlich.